The Effectiveness of Implementation of The Nearpod Application on Students’ Vocabulary Achievement at Junior High School - Yeyet Kusmiati; Hidayat, Hendi; Waloyo , Edy (STIT Buntet Pesantren Cirebon, 2024)
This study aimed to evaluate the effectiveness of the Nearpod application in enhancing students' vocabulary. Utilizing a quasi-experimental design, quantitative methods were employed, and data were collected through pre-tests and post-tests. The findings revealed a significant improvement in vocabulary scores among students using Nearpod. The experimental group showed an increase in average scores from 51.13 (pre-test) to 75.97 (post-test), with a maximum score of 90 and a minimum score of 60. In contrast, the control group's scores increased from 52.03 to 72.22, with a maximum score of 85 and a minimum score of 55. The T-test results indicated a higher post-test score in the experimental group compared to the control group. The standard deviation for the experimental group was 8.604, and for the control group, it was 7.763. The average standard error was 1.587 for the experimental group and 1.265 for the control group. The independent sample t-test showed t (df=56) = 2003 with a p-value of 0.945, leading to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). These results suggest that the Nearpod application is effective in improving students' vocabulary achievement.